The efficiency of a multicomponent training for prospective memory among healthy older adults: a single-blind, randomized controlled within-participants cross-over trial - Farzin, Azin; Ibrahim, Rahimah; Madon, Zainal; Basri, Hamidon (Lippincott, Williams & Wilkins, 2018)
Objective: The main objective of the present trial was to evaluate the efficiency of a preventative multicomponent prospective memory training among healthy older adults. Design: This study was a two-arm within-participants trial with 4- and 12-wk follow-ups. Allocation ratio was 1:1, and pretraining and posttraining measurements were included. A total number of 25 healthy older adults were enrolled (mean = 63.32, SD = 4.44). Participants were randomly allocated into two conditions: (a) prospective memory training: participants underwent a multicomponent prospective memory training, and (b) control: participants were not contacted during the training phase. After the training phase was finished, participants crossed over to undergo the condition they did not experience before. The differences between pretraining and posttraining measures of prospective memory, activities of daily living, negative mood (depression), and anxiety were assessed. All changes in the measurements were analyzed using general linear method. This trial is registered at https://www.isrctn.com (#ISRCTN57600070). Results: Multicomponent prospective memory training program was significantly effective on both subjective and objective prospective memory performances among healthy older adults. Moreover, the training had significant positive effects on activities of daily living (independence) among participants. In addition, negative mood and anxiety levels were reduced after the training was finished. Conclusions: This multicomponent prospective memory training improved prospective memory performance and activities of daily living and reduce negative mood (depression) and anxiety levels among healthy older adults.